Copper Stress on Photosynthesis of Black Mangle (Avicennia germinans) - GONZALEZ-MENDOZA,DANIEL (2013)
The effects of copper toxicity on the photosynthetic activities of Avicennia germinans was investigated using two CuSO4 concentrations (0.062 and 0.33 M) added in Hoagland's solution in an aerated hydroponic system. Photosynthesis and chlorophyll fluorescence were measured after 30 h of copper stress. Results obtained in this study show that increasing levels of Cu+2 of 0.062 and 0.33 M Cu+2 resulted in a general reduction of the stomatal conductance (28 and 18%, respectively) and 100% of inhibition of net photosynthesis. Additionally, at these concentrations of Cu+2, reductions of chlorophyll fluorescence parameters were also observed. These changes suggested that the photosynthetic apparatus of Avicennia germinans was the primary target of the Cu+2 action. It is concluded that Cu+2 ions causes a drastic decline in photosynthetic gas exchange and Chlorophyll fluorescence parameters in A. germinans leaves.